Robotic Sailing 2015 Proceedings of the 8th International Robotic Sailing Conference - Friebe, Anna.; Haug, Florian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the cutting edge developments within a broad field related to robotic sailing. The contributions were presented during the 8th International Robotic Sailing Conference, which has taken place as a part of the 2015 World Robotic Sailing Championships in Mariehamn, Åland (Finland), August 31st - September 4th 2015. Since more than a decade, a series of competitions such as the World Robotic Sailing Championship have stimulated a variety of groups to work on research and development around autonomous sailing robots, which involves boat designers, naval architects, electrical engineers and computer scientists. While many of the challenges in building a truly autonomous sailboat are still unsolved, the books presents the state of the art of research and development within platform optimization, route and stability planning, collision avoidance, power management and boat control.
Part I Sailboat Platforms and Applications -- Part II Mission Planning, Localization and Obstacle Avoidance -- Part III Controllers and Sensors.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Control, Robotics, Automation; Artificial Intelligence